Value Transformation : History of the Topeng Ireng in Magelang 2010-2022 - Nevanndaa, Lina Anggun Nevanda (Journal of Islamic History, 2023)
This study explains the transformation of Topeng Ireng art in Keditan Hamlet, Magelang Regency in 2010-2022. The author limits the problem to two things, namely: (1) How was the early history of the establishment of Topeng Ireng in Keditan Village? (2) How did the modernization of Topeng Ireng art enter Keditan Village? This study uses a historical research method, namely: (1) Heuristics is looking for the necessary sources, both written and oral sources. Written sources can be in the form of books, journals and theses. While oral sources can be done through interviews with historical actors, (2) Source criticism or verification through source triangulation and method triangulation, (3) Interpretation or interpretation, (4) Historiography or writing history. The results of this study found that the development of Topeng Ireng art cannot be separated from the development of values ​​in society, as an important part of culture. The Topeng Ireng art of the Siswo Tresno Budoyo Association (PSTB) of Keditan Village was established in 2010. In 2019, the Topeng Ireng art in Keditan Village had lost its mystical nature. As time went by, in 2022 the music genre accompanying the Topeng Ireng dance became SKA DUT (Ska Dangdut).